2022
DOI: 10.1021/acsami.2c08192
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Charge on the Fabrication of Hierarchical Mn-Based Prussian Blue Analogue for Capacitive Desalination

Abstract: Multiple and hierarchical manganese (Mn)-based Prussian blue analogues obtained on different substrates are successfully prepared using a universal, facile, and simple strategy. Different functional groups and surface charge distributions on carbon cloth have significant effects on the morphologies and nanostructures of Mn-based Prussian blue analogues, thereby indirectly affecting their physicochemical properties. Combined with the advantages of the modified carbon cloth and the nanostructured Mn-based Prussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…In this work, the authors were committed to generating Ni foam loaded with different Cu contents by adjusting the substitution time and then modulating the structure and morphology of the integrated rGO/ CNF electrode, thereby featuring it with a porous network and more accessible surface area. As a result, the optimal rGO/ CNF electrode contributed to the increased surface areas and facilitated ion transport, thereby leading to delivery of an excellent deionization performance with a desalination capacity of 84.6 mg g À1 (2.23 times higher than that of rGO with the single Ni substrate), a satisfactory removal rate of 4.88 mg g À1 min À1 , and an acceptable long-term stability (over 91% capacity retention after 20 cycles) in a 250 mg L À1 NaCl solution at 1.2 V. In addition, Zhang et al 144 synthesized manganese (Mn)-based Prussian blue analogues (MPBs) loaded on various tailored substrates (e.g., the acid-treated carbon cloth (ACC), F-doped carbon cloth (FCC), chitosan-coated carbon cloth (CCC), and N-doped carbon cloth (NCC)) to investigate the effects of different functional groups and surface charge on the carbon cloth towards desalination performance. Specifically, the different monolithic MPB/CC electrodes were fabricated using a facile chemical bath deposition method, and directly utilized as the CDI electrode in a hybrid CDI system (Fig.…”
Section: Reviewmentioning
confidence: 99%
“…In this work, the authors were committed to generating Ni foam loaded with different Cu contents by adjusting the substitution time and then modulating the structure and morphology of the integrated rGO/ CNF electrode, thereby featuring it with a porous network and more accessible surface area. As a result, the optimal rGO/ CNF electrode contributed to the increased surface areas and facilitated ion transport, thereby leading to delivery of an excellent deionization performance with a desalination capacity of 84.6 mg g À1 (2.23 times higher than that of rGO with the single Ni substrate), a satisfactory removal rate of 4.88 mg g À1 min À1 , and an acceptable long-term stability (over 91% capacity retention after 20 cycles) in a 250 mg L À1 NaCl solution at 1.2 V. In addition, Zhang et al 144 synthesized manganese (Mn)-based Prussian blue analogues (MPBs) loaded on various tailored substrates (e.g., the acid-treated carbon cloth (ACC), F-doped carbon cloth (FCC), chitosan-coated carbon cloth (CCC), and N-doped carbon cloth (NCC)) to investigate the effects of different functional groups and surface charge on the carbon cloth towards desalination performance. Specifically, the different monolithic MPB/CC electrodes were fabricated using a facile chemical bath deposition method, and directly utilized as the CDI electrode in a hybrid CDI system (Fig.…”
Section: Reviewmentioning
confidence: 99%
“…), [61–64] Prussian blue/Prussian blue analogues (PB/PBAs, e. g. NiHCF, CuHCF, CoHCF, MnHCF, FeHCF, etc. HCF=hexacyanoferrate), [65–68] and redox‐active polymers or organic molecules [69–71] …”
Section: Faradaic Electrode Materials For CDImentioning
confidence: 99%
“…), [61][62][63][64] Prussian blue/Prussian blue analogues (PB/PBAs, e. g. NiHCF, CuHCF, CoHCF, MnHCF, FeHCF, etc. HCF = hexacyanoferrate), [65][66][67][68] and redox-active polymers or organic molecules. [69][70][71] Several advantages of intercalation-type Faradaic materials compared to the traditional carbon electrodes can be pointed as follows: (i) high SAC, (ii) low energy consumption, (iii) minimum co-ion expulsion/high charge efficiency, and (iv) size/ charge selective separation of ions.…”
Section: Charge Efficiency (λ) and Energy Consumption (E)mentioning
confidence: 99%
“…Therefore, it remains important to develop PBA materials with remarkable electrochemical desalination performance, and excellent cycling stability. To improve the desalination capacity and/or stability of such electrodes, integrating them with carbon-based materials such as reduced graphene oxide (rGO), [23] graphene aerogel (GA), [24] 3D carbon nanosheet networks (3DC), [25] carbon cloth, [26,27] and carbon nanotubes (CNTs) [28] is a feasible and promising strategy. A recent report has demonstrated an SAC as high as 107.5 mg g −1 for NiHCF@3DC-2//activated carbon electrodes in a hybrid CDI (HCDI) cell with an influent of 20 000 mg L −1 and a cell voltage of 1.2 V. [25] Besides, incorporating PBAs with other non-carbon materials such as Nafion, [29] and Ti 3 C 2 T x MXene [30] can also improve their stability and/or adsorption capacity toward sodium ions.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, it was found that the desalination performance of PBA electrodes can be efficiently enhanced by compositional optimizing [31] and/or structural tailoring. [26,27,32] A recent study has shown that PBA nanoframes with high crystallinity and a large contactable surface area show remarkable rate performance and cycling stability for sodium/lithium-ion insertion/extraction. [33] Rehman et al found that high-quality NiHCF (also with high crystallinity) exhibited a high specific capacity and notable cycling stability without noticeable fading in capacity retention after 1200 cycles, which makes such PBA a promising long-life cathode material for sodium-ion batteries.…”
Section: Introductionmentioning
confidence: 99%